2011
DOI: 10.1088/1468-6996/12/3/034411
|View full text |Cite
|
Sign up to set email alerts
|

Competitive adsorption of fibronectin and albumin on hydroxyapatite nanocrystals

Abstract: Competitive adsorption of two-component solutions containing fibronectin (Fn) and albumin (Ab) on hydroxyapatite (HAp) nanocrystals was analyzed in situ using the quartz crystal microbalance with dissipation (QCM-D) technique. Adsorption of the one-component protein (Fn or Ab) and the two-component proteins adjusted to different molar ratios of Fn to Ab at a fixed Fn concentration was investigated. The frequency shift ( f ; Hz) and the dissipation energy shift ( D) were measured with the QCM-D technique, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…For the HAp surface, Ab and Fn adsorption in a complex fashion has been reported by two-component adsorption. 70 As judged from the ΔD-Δf plots in Figure 5, Ab interacts with Fn due to interfacial changes in elasticity using Voigt-based viscoelastic analysis and an antibody-binding technique.…”
Section: Multi-component Toward Serum Protein Studymentioning
confidence: 99%
See 1 more Smart Citation
“…For the HAp surface, Ab and Fn adsorption in a complex fashion has been reported by two-component adsorption. 70 As judged from the ΔD-Δf plots in Figure 5, Ab interacts with Fn due to interfacial changes in elasticity using Voigt-based viscoelastic analysis and an antibody-binding technique.…”
Section: Multi-component Toward Serum Protein Studymentioning
confidence: 99%
“…With an increase in the albumin concentration, the ΔD sat /Δf sat value decreased from − 14.5 ± 1.9 × 10 -8 to − 6.3 ± 1.6 × 10 -8 , indicating that the viscoelastic behavior of the Anfibronectin compound adlayer changed to elastic with increasing albumin concentration. Reprinted with permission from Tagaya et al70 …”
mentioning
confidence: 99%
“…14 Fn is known to modulate a number of cell behaviors, including adhesion, migration, and differentiation. [20][21][22][23][24] Sousa et al have investigated the influence of Fn-Alb coadsorbed layers (on titania) on the adhesion and morphology of preosteoblastic MC3T3-E1 cells, and note that while cell adhesion generally correlates with extent of Fn adsorption, the Fn effect can be enhanced in the presence of a modest amount of Alb. Blood proteins such as albumin are generally much more concentrated in biological solution than are matrix proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In the biomedical field, it is suggested that the high strength of CF can allow its use as implants, so that the coating with a biocompatible apatite (for example, hydroxyapatite (Hap): Ca 10 (PO 4 ) 6 (OH) 2 ) layer is needed. [61][62][63][64][65] Furthermore, magnetic nanoparticle (MNP) composites with a magnetite (Fe 3 O 4 ) core and HAp coating were prepared by using a precipitation method and a subsequent hydrothermal treatment as shown in Figure 4B. [60] We have also conducted studies on interfacial phenomena using HAp nanocrystals, including the investigation of the protein adsorption states on the surfaces.…”
Section: Biocompatible Materialsmentioning
confidence: 99%